2018
DOI: 10.1038/s41380-018-0273-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, cortical thickness and neural activity predictors of future affective lability in youth at risk for bipolar disorder: initial discovery and independent sample replication

Abstract: We aimed to identify markers of future affective lability in youth at bipolar disorder risk from the Pittsburgh Bipolar Offspring Study (BIOS) (n=41, age=14, SD=2.30), and validate these predictors in an independent sample from the Longitudinal Assessment of Manic Symptoms study (LAMS) (n=55, age=13.7, SD=1.9). We included factors of mixed/mania, irritability, and anxiety/depression (29 months post MRI scan) in regularized regression models. Clinical and demographic variables, along with neural activity during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 73 publications
(82 reference statements)
0
12
0
Order By: Relevance
“…17 There are some limitations to these meta-analyses that may have led to an overestimation of the relationship between RPAs and depression. In particular, only two studies provide out-of-sample tests of prediction accuracy (19,28) (Table S4); the others should be considered tests of within-sample association and would overestimate predictive performance as defined in Box S2. Open science practices improve reliability and reduce positive bias in published reports (37,38), but they are not yet broadly adopted and were not observed in the reviewed studies (Table S5).…”
Section: Longitudinal Associationmentioning
confidence: 99%
“…17 There are some limitations to these meta-analyses that may have led to an overestimation of the relationship between RPAs and depression. In particular, only two studies provide out-of-sample tests of prediction accuracy (19,28) (Table S4); the others should be considered tests of within-sample association and would overestimate predictive performance as defined in Box S2. Open science practices improve reliability and reduce positive bias in published reports (37,38), but they are not yet broadly adopted and were not observed in the reviewed studies (Table S5).…”
Section: Longitudinal Associationmentioning
confidence: 99%
“…Only potential interactions between non-zero main effects are considered. We included multiple actigraphy covariates (i.e., Non-zero predictors selected by group-lasso models were entered into linear regression models, as in prior reports 89,90 . R-squared was computed to estimate variance explained by the full model as well as groups of predictors (i.e., demographics, neuroimaging measures, actigraphy covariates).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…A negative correlation was found between altered right FFG MRI measurements and fearful FER accuracy in patients with FSZ, especially altered mfALFF of the right FFG. A large number of studies have shown that the FFG is associated with FER in different disorders, including bipolar disorder 37 , autism spectrum disorder 38 , and traumatic brain injury 39 . The FFG, especially the right FFG, supports face processing, social communication, and facial identity processing 40 .…”
Section: Discussionmentioning
confidence: 99%